2008
DOI: 10.1038/sj.bjc.6604829
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan plus carboplatin for patients with carcinoma of unknown primary site

Abstract: Carcinoma of unknown primary site (CUP) is rarely encountered in clinical practice and optimal chemotherapy has not yet been established. This phase II study was conducted to evaluate the efficacy and toxicity of combined irinotecan þ carboplatin therapy in chemotherapy-naive patients with CUP. Irinotecan was administered at 60 mg m À2 as a 90-min intravenous infusion on days 1, 8 and 15. Carboplatin was administered at an area-under-the curve of 5 mg ml À1 min as a 60-min intravenous infusion on day 1. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…There was one consecutive case series study (Gill et al , 1991) and the other 23 studies were single arm clinical trials (Raber et al , 1991; Briasoulis et al , 1998, 2000, 2008; Parnis et al , 2000; Greco et al , 2001, 2002; Guardiola et al , 2001; Macdonald et al , 2002; Balana et al , 2003; Mukai et al , 2003, 2010; Park et al , 2004; Piga et al , 2004; Pouessel et al , 2004; El-Rayes et al , 2005; Pittman et al , 2006; Schneider et al , 2007; Pentheroudakis et al , 2008; Hainsworth et al , 2009; Schuette et al , 2009; Yonemori et al , 2009; Moller et al , 2010). Three trials (Briasoulis et al , 1998, 2000; Pentheroudakis et al , 2008) also involved a small proportion of favourable CUP patients in their studies, and we extracted the data only from the unfavourable subset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was one consecutive case series study (Gill et al , 1991) and the other 23 studies were single arm clinical trials (Raber et al , 1991; Briasoulis et al , 1998, 2000, 2008; Parnis et al , 2000; Greco et al , 2001, 2002; Guardiola et al , 2001; Macdonald et al , 2002; Balana et al , 2003; Mukai et al , 2003, 2010; Park et al , 2004; Piga et al , 2004; Pouessel et al , 2004; El-Rayes et al , 2005; Pittman et al , 2006; Schneider et al , 2007; Pentheroudakis et al , 2008; Hainsworth et al , 2009; Schuette et al , 2009; Yonemori et al , 2009; Moller et al , 2010). Three trials (Briasoulis et al , 1998, 2000; Pentheroudakis et al , 2008) also involved a small proportion of favourable CUP patients in their studies, and we extracted the data only from the unfavourable subset.…”
Section: Resultsmentioning
confidence: 99%
“…Two independent reviewers evaluated the responses, which were the primary outcome of the study in only two studies (Culine et al , 2003; Moller et al , 2010). In all, 14 studies reported prospective calculation of the study size (Greco et al , 2002; Macdonald et al , 2002; Pouessel et al , 2004; El-Rayes et al , 2005; Palmeri et al , 2006; Pittman et al , 2006; Schneider et al , 2007; Pentheroudakis et al , 2008; Hainsworth et al , 2009, 2010; Huebner et al , 2009; Schuette et al , 2009; Yonemori et al , 2009; Mukai et al , 2010). Among the RCTs, only one study had a clear description of the method of allocation concealment (Assersohn et al , 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Alternative non-taxane containing doublets and triplets have also been tested with no apparent improvement in clinical outcomes. [18][19][20][21] Most of these studies were in a younger patient population, so it is not clear whether such regimens are appropriate in elderly patients.…”
Section: Discussionmentioning
confidence: 97%
“…Phase II studies evaluating these agents combined with a platinum compound, including clinical trials in patients with CUP, were successively performed and reported. [18][19][20][21][22] Many of these studies obtained a response rate of about 30% and an overall survival of less than 10 months. [18,19] In these studies, an overall survival of longer than 10 months was obtained in patients who received combined chemotherapy with a platinum preparation plus taxane.…”
Section: Discussionmentioning
confidence: 99%